Breathing reserve and lung function in female elite runners - Kyte, F.G.; Kyte, K.H.; Skinstad, L.; Hisdal, J.; Stensrud, T. (Sports, 2025)
Breathing reserve (BR) is the remaining proportion of achievable minute ventilation that remains unutilized at total exhaustion during exercise. Previous studies have found a smaller BR in endurance-trained athletes compared to untrained controls. However, most of these studies have examined men. Given that women have a greater ventilatory limitation than stature-matched men, the present cross-sectional study aimed to investigate how this sex difference influences BR and lung function tests in endurance-trained females compared to matched, untrained females. To obtain further insight, we also aimed to investigate whether VO2max serves as a predictor of BR. We examined 15 female elite runners and 15 healthy, matched female controls aged 24-33 years with regard to pulmonary function, MVV, VEmax, BR, and VO2max. The elite runner group had a median BR of 5%, while that of the controls was 21%, representing a significant difference. Lung function tests showed no differences between the two groups. A moderate association was found between VO2max and BR. The female elite runners demonstrated a lower BR than the group of matched, untrained controls, which was lower than that found for male elite athletes in previous studies. This may indicate a greater ventilatory demand in female relative to male endurance athletes.